Nannofossil events of Maastrichtian sediments from DSDP Hole 74-525A in the South Atlantic (Table 2) - Nicolas Thibault; Silvia Gardin (PANGAEA, 2007)
The phytoplankton response (calcareous nannofossils) to the Late Maastrichtian climate evolution is investigated in the South Atlantic DSDP Hole 525A and compared to published geochemical and micropaleontological data. The results point to a succession of dramatic climatic fluctuations. “Cool-water indicators” (Ahmuellerella octoradiata, Kamptnerius magnificus and Nephrolithus frequens) suggest cool surface water conditions prevailed during Chron C30n. At the top of C30n, their sudden drop in abundance, the last occurrence of B. constans and the concomitant increase in the tropical species Micula murus suggest warming and lower surface water productivity. An M. murus acme within Chron C29r reflects maximum warming. During the last 100 kyr of the Maastrichtian, the decrease in M. murus and increase in cool-water indicators reflect rapid cooling with the cool climate persisting over. The calcareous nannoplankton response to climate change correlate with similar findings in the Equatorial Atlantic Hole 1258A and parallels the stable isotope record of planktic and benthic foraminifera of DSDP Hole 525A as well as the decline in 187Os/188Os. Comparison of this marine record and the continental climate record in North America suggests a link between Deccan volcanism and the late Maastrichtian warm event.
Supplement to: Thibault, N; Gardin, S (2007): The late Maastrichtian nannofossil record of climate change in the South Atlantic DSDP Hole 525A. Marine Micropaleontology, 65(3-4), 163-184, https://doi.org/10.1016/j.marmicro.2007.07.004